Marriage in Crisis: Causes and Consequences of Divorce among Young Couples in Mtoni Ward, Zanzibar - Bakari Khatib Faki; Isbandi Rukminto Adi (JSW (Jurnal Sosiologi Walisongo), 2026)
Divorce among young couples in urban Zanzibar has emerged as a critical social welfare concern shaped by Islamic marital norms, rapid urbanization, and shifting gender dynamics in Mtoni Ward, West District “A.” The 2022 Population and Housing Census reports a 6.2% divorce rate in the Urban West Region, with women disproportionately affected, yet existing literature remains theoretically limited. This study employs a qualitative desk review of secondary data, integrating peer-reviewed literature and census evidence, guided by Social Exchange Theory, Maslow’s Hierarchy of Needs, and Community Development Theory. Findings indicate that unemployment, economic insecurity, emotional neglect, poor communication, and weakening community mediation structures jointly accelerate marital dissolution. The study demonstrates that divorce is a structurally embedded social welfare issue rather than an individual failure. It calls for gender-responsive interventions, including premarital education, economic empowerment, and sustainable post-divorce support systems.